Directly replaces of a minors and “exemplary” of a disability person: The patrimony of a persons with disability or minors 14 years old - Mª Fernanda Moretón Sanz (Revista Sobre la Infancia y la Adolescencia)
This research study the law, the jurisprudence and the law literatury of aspects of replaces of a minors and “exemplary” of a disability persons. It is fact that used by the testator, have different impact about the patrimony of de minors and persons whit disability. In the substitution or replaces, the object will depend on the means the testator deciding on the disposal heritage. Specifically, despite certain resistance from legal thought and case-law, in the substitution of a minor and in exemplary replace, the substitute (parent or legal representative) may dispose of all the of the person substituted (child under 14 years of age or legal incapacitated person). Therefore, both types of substitution affect to the persons substituted and the patrimony of them